6(2x+8)-2=2(x-2)

Simple and best practice solution for 6(2x+8)-2=2(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2x+8)-2=2(x-2) equation:



6(2x+8)-2=2(x-2)
We move all terms to the left:
6(2x+8)-2-(2(x-2))=0
We multiply parentheses
12x-(2(x-2))+48-2=0
We calculate terms in parentheses: -(2(x-2)), so:
2(x-2)
We multiply parentheses
2x-4
Back to the equation:
-(2x-4)
We add all the numbers together, and all the variables
12x-(2x-4)+46=0
We get rid of parentheses
12x-2x+4+46=0
We add all the numbers together, and all the variables
10x+50=0
We move all terms containing x to the left, all other terms to the right
10x=-50
x=-50/10
x=-5

See similar equations:

| 692x+8)-2=2(x-2) | | -15x+4-4(x-1)=-4x-(14x-3)+4 | | -(4-7x)=23-2x | | 3=45.7,12=x | | s-1.9*15=4.6 | | 3=45.7,6=x | | 3=45.7,6+x | | s-1.6*15=4.6 | | X=48x+37 | | x3+x2+-21x+-45=0 | | 3y/y+1=7-3/y+1 | | 2(4+2v)=-6(v-8) | | -33=5v+4(v+3) | | −6y2+y-3=0 | | 3(x-2)=8x+19 | | 6y-3y-15=46.95 | | -8(d+1)-d-12=-9(d+3)+7 | | (X)=8x+5x-4 | | 3x-7/2+3-5x/3=3-6x/5 | | .66(9b-27)=36342 | | -7x+7=-7(3x-5) | | (X)=14x-4x+6x-3 | | -24-3n=3(-4n+3)+3 | | X=24x+37 | | -5/6+y=-9/43 | | -5/6+y=-9/4 | | -2/3+y=-1/2 | | -2x+7x-7=5(x-5)-2 | | x2+3x-72=0 | | (X)=7x+4x+6 | | –8=32–5q | | y/3+2/3=y/2+3/2 |

Equations solver categories